Development of high pressure spray triggering - Wan Mohd Rashdan, Wan Mansor (2012)
This project presents the study about development of high pressure spray triggering and control in a direct injection gasoline injector of a gasoline engine. The objectives of the study is to develop injection system using a parameters of time and pressure in order to identify the spray characteristics including spray angle, spray tip penetration and spray width. The scopes of this research is choosing control system EFI in type of injection, setup test rig for experimental using high pressure chamber and develop control and triggering system in order to control the timing and delay of the injector. After test rig fabrication is done and all equipment has been setup, experiment is done by supplying pressure from high pressure fuel pump to fuel injector that attach to high pressure chamber. Ambient temperature was set to 300 K and ambient pressure is 10 kpa, 20 kpa, 30 kpa and 40 kpa. Simple triggering and control has been developing using MATLAB Simulink and the DAQ software result was analyzed due to sample of calculation.